An introduction to numerical methods in low-dimensional quantum systems - Malvezzi, A. L. (Sociedade Brasileira Fisica, 2003)
This is an introductory course to the Lanczos Method and Density Matrix Renormalization Group Algorithms (DMRG), two amona the leading numerical techniques applied in studies of low-dimensional quantum models. The idea of studying the models on clusters of a finite size in order to extract their physical properties is briefly discussed. The important role played by the model symmetries is also examined. Special emphasis is given to the DMRG.